(untitled) (Journal of Informatics Education and Research, 2025)
Recruitment plays a pivotal role in organizational success, directly influencing the quality of the workforce. In today’s competitive business environment, the process of attracting and selecting top talent has evolved significantly, particularly with the advent of e-recruitment. This paper examines the impact of e-recruitment on talent acquisition, with a focus on how technological advancements, particularly the Internet and social media platforms, have reshaped recruitment strategies. Online job boards, career portals, and professional social media platforms like LinkedIn have become essential tools for connecting employers with potential candidates. These digital tools facilitate the recruitment process by providing greater accessibility, cost-effectiveness, and speed compared to traditional methods. In the context of IT companies, such as Tech Mahindra, Infosys, and Awareness, e-recruitment has proven to be an effective strategy in attracting skilled professionals, especially in the high-demand IT sector. The study explores the benefits of e-recruitment, including wider candidate pools, faster hiring processes, and reduced recruitment costs. Additionally, it discusses the advantages and challenges of using social media platforms for recruitment, highlighting how organizations can leverage these technologies to enhance their hiring strategies. Finally, the paper identifies future research avenues and the evolving role of Human Resource Management (HRM) in a digitalized world, underscoring the importance of balancing technological tools with human judgment in the recruitment process.